Analisis Rantai Pasok Benih Padi UD Agro Tani Kecamatan Soko Kabupaten Tuban - Yudha, Danang Ananda; Noor Djohar; Aji Sugiarto (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2024)
This research aims to determine product flow, financial flow and supply chain information flow as well as determine the marketing efficiency of the rice seed supply chain at UD Agro Tani. Cluster Random Sampling method, with a total of 26 respondents. The data collection method uses observation, interviews and documentation methods. Data analysis uses farmer's share analysis and marketing efficiency. In the channel 1 pattern the total margin is IDR. 6,200/Kg and channel pattern 2 total margin Rp. 5,700/Kg, total costs incurred by UD Agro Tani Rp. 1,500/kg includes production and transportation costs. The farmer's share value obtained by partner farmers in channel 1 pattern was 48.33% and channel 2 pattern was 50.43%. The percentage value shows that the flow of the rice seed supply chain is said to be efficient because the farmer's share value is <40%. Marketing efficiency in channel pattern 1 was found to be 12.5% ​​and channel pattern 2 was obtained at 13.04%, where the supply chain efficiency was said to be efficient because it was <33%. So the results of farmer's share and efficiency marketing of UD Agro Tani's rice seed supply chain are efficient to do.